(untitled) (Applied Biological Research, 2016)
Mast cell tumours are usually subcutaneous masses found in adult dogs with specific breed predis position. These are either benign or malignant and may metastasize later in their coarse but their true metastatic potential is not entirely known (Webster et al., 2007; Welle et al., 2008). The prognosis of canine mast cell tumours depends upon the degree of involvement and stage of neoplasia. However, the involvement of canine mammary tumour by mast cell neoplasia seems to be unusual and not reported so far. The present case report deals with a unique case of mammary mastocytoma.